The Effect of Listen-Read-Discuss (LRD) Strategy on Students Reading Comprehension in Ninth Grade at SMP Widya Sakti - Ni Made Putri Widya Astari; I Putu Andre Suhardiana; Ni Putu Ratni (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study aimed to determine whether there was a significant effect of the Listen–Read–Discuss (LRD) strategy on students’ reading comprehension in ninth grade at SMP Widya Sakti Denpasar. This study employed a quantitative approach with a quasi-experimental design using a non-equivalent control group design. The participants of this study were ninth-grade students of SMP Widya Sakti Denpasar, consisting of one experimental class and one control class with a total of 36 students in each class. The instruments used in this research were pre-test and post-test in the form of multiple-choice reading comprehension tests on narrative texts. The data were analyzed using descriptive and inferential statistical analysis, including normality test, homogeneity test, Mann–Whitney U test, Independent Sample T-test, and ANCOVA. The findings showed that the students taught by using the Listen–Read–Discuss (LRD) strategy achieved better reading comprehension scores than those taught by using the conventional method. The findings revealed that students who were taught using the Listen-Read-Discuss (LRD) strategy achieved better reading comprehension performance than those who were taught through the conventional direct instruction method. The experimental group obtained a higher mean score (78.05) compared to the control group (72.67). In addition, the ANCOVA analysis showed a significance value of 0.000, which was lower than 0.05, indicating a significant effect between the two groups. In conclusion, the Listen–Read–Discuss (LRD) strategy was effective in improving students’ reading comprehension of narrative texts. Therefore, English teachers are suggested to apply the LRD strategy as an alternative strategy in teaching reading comprehension, and future researchers are recommended to conduct further studies with different text types and educational levels.